White collar workers in the 50's: A lack of coverage and responsibility by adult education - Paula Burk Uhlir (Adult Education Research Conference, 1994)
Adult Education (AE) was designed as a conduit of information from the AEA to their members in all areas of adult education and as a forum for debate and discussion concerning those issues. During it's first decade of operation AE published articles chosen by its executive committee based on themes selected by the committee. Because the committee was void of direct representation with interests in corporations business and industry, AE was not the representative voice it could have been in the field of adult education in business and industry during the 1950s.